Enhancing mating performance after juvenile hormone treatment in Anastrepha fraterculus: A differential response in males and females acts as a physiological sexing system - Segura, Diego Fernando (2009)
Methoprene (a mimic of juvenile hormone) treatment can reduce the time required for sexual maturation in Anastrepha fraterculus (Wiedemann) (Diptera: Tephritidae) males under laboratory conditions, supporting its use as a treatment for sterile males within the context of the sterile insect technique (SIT). We evaluated sexual behaviour, mating competitiveness of methoprene-treated males, and female readiness to mate after methoprene-treatment in field cages. The study involved two strains of A. fraterculus from Argentina and Peru, which show several polymorphisms in relation to their sexual behaviour. We also analyzed whether methoprene treatment affected male and/or female behaviour in the same way in these two strains. Methoprene-treated males were equally competitive with untreated mature males, and became sexually competitive 6 days after emergence (3-4 days earlier than untreated males). In contrast, methoprene did not induce sexual maturation in females or, at least, it did not induce a higher rate of mating in 7-day-old females. These results were observed both for the Argentina and the Peru strains. Altogether, our results indicate that methoprene treatment produces sexually competitive males in field cages. In the absence of a genetic sexing system, and when sterile males and females of A. fraterculus are released simultaneously, the fact that females do not respond as do males to the methoprene treatment acts as a physiological sexing effect. Therefore, in the presence of mainly sexually immature sterile females, released sexually mature sterile males would have to disperse in search of wild fertile females, thereby greatly reducing matings among the released sterile insects and thus enhancing sterile insect technique efficiency.